Assessment of WRF microphysics and cumulus parameterizations in simulating heavy rainfall events over Badulu Oya catchment, Sri Lanka. Issue 12 (23rd November 2022) - Gimhan, P. G. S.; Neluwala, Panduka; Acierto, Ralph Allen; Raghavan, Srivatsan V.
Abstract: Extreme rainfall events leading to severe hydrological impacts warrant an accurate prediction of such events not only on time but also in magnitude. Sri Lanka is a South Asian country that is frequently affected by severe tropical storms. The primary aim of this study was to improve heavy rainfall events forecast during the North-East monsoon over the Badulu Oya catchment, Sri Lanka. This aim was accomplished by simulating precipitation for two extreme North-East monsoon rainfall events using the Weather Research and Forecasting (WRF-ARW) model. A detailed comparison was made between the 24-h spatial distribution of model rainfall and observations obtained from rainfall gauges. Verification was evaluated based on three deterministic approaches. Each rainfall event was simulated multiple times using 15 different parameterization scheme combinations including six microphysics and four cumulus schemes at a 3 km grid resolution. The filtered best model combinations were validated using observations from another two heavy North-East monsoon rainfall events. The key finding from these evaluations was that model configurations with WSM5, WSM6, Kessler and WDM6 microphysics, and KF, BMJ and MKF cumulus schemes displayed the overall best performances. Therefore, these combinations have a good potential for operational use in numerical weather prediction over the said catchment. HIGHLIGHTS: Extreme precipitation events within the North-East monsoon over Badulu Oya catchment, Sri Lanka were simulated using the WRF-ARW model. Sensitivity studied to MP (Ferrier, WSM3, WSM5, WSM6, Kessler, WDM6) and CU (KF, BMJ, MKF, GF) schemes combinations. Simulations were evaluated with field observations. Combinations of WSM5, WSM6, Kessler, WDM6 along with KF, BMJ and MKF schemes displayed the overall best performances. Graphical Abstract